Does left atrial appendage morphology have any impact on the results of percutaneous closure?. (25th November 2020) - Constantin, V; Cinaud, A; Brigadeau, F; Lepillier, A; Pierre, B; Deharo, J.C; Defaye, P; Montalescot, G; Fauchier, L; Mansourati, J
Abstract: Introduction: Transcatheter left atrial appendage (LAA) occlusion is an alternative treatment in patients with atrial fibrillation (AF), high CHADSVASC Score and a contra-indication to anticoagulants. This retrospective cohort study aims to evaluate the impact of LLA morphology on procedure outcomes. Methods: Patients from eight French centers who underwent left atrial appendage occlusion from February 2012 to January 2017 were included in this retrospective cohort study. LLA morphology was described by preoperative cardiac computed tomography (CT). Clinical data and Transoesophageal echocardiography (TEE) or CT results were collected during follow-up. Results: Among 469 included patients, LAA morphologies were described in 215 cases 45.8%), 150 patients (70%) were implanted with Watchman devices, 57 (26%) with Amplatzer devices and 8 procedures (4%) failed. LAA Morphology was Chicken Wing (34%), Windsock (45%), cauliflower (18%) and 3% had another morphology including Cactus. There was no difference in patient characteristics between the different morphology groups. Mean follow-up was 9.6±11 months, during which 190 patients underwent LAA imaging (TEE in 171 and CT in 19 patients). There was no significant difference in the failure rate (p=0.72), duration of the procedure (p=0.065), peri-device leak (p=0.83) device-related thrombus (p=0.96) and the occurrence of stroke (p=1) during follow-up. Conclusion: LLA morphology did not influence complication occurrence after occlusion in this cohort. Funding Acknowledgement: Type of funding source: None